Advancements in Biomarkers for Assessing Dialysis Efficiency: A Comprehensive Review - M, Roja; Bharath Kumar G R; Vishnu MG; Rahul E (Gayaku Publisher, 2024)
This review discusses the recent development in biomarkers of dialysis efficiency in patients suffering from CKD and ESRD. The systematic review covered literature in the years 2019 to 2024 with emerging biomarkers and their clinical application along with innovative ways to detect the biomarkers. Traditional biomarkers are the urea reduction ratio (URR) and Kt/V, while newer biomarkers like β2-microglobulin, cystatin C, and fibroblast growth factor 23 (FGF23) receive increased recognition regarding their ability to better present patient health. These biomarkers could dramatically enhance personalization of treatment through precise adjustments in dialysis regimens that may promote better patient outcomes. All of these developments are further driven by technological advancements, for instance, optical sensors and point-of-care devices, for real-time and more sensitive detection of biomarkers. Indeed, the integration of these new biomarkers and technologies may revolutionize dialysis patient monitoring, enabling more tailored and effective strategies.